Histomorphometric Changes of Pancreatic Islets with Advancing Age – A Postmortem Study in A Bangladeshi Male Population - Shahriah, S; Nurunnabi, ASM; Begum, GN; Kabir, R (Nepal Journal of Medical Sciences, 2014)
Background: We proposed this study to see the difference in number and diameter of the islets of Langerhans of the pancreas with increasing age in Bangladeshi males, as male population is more prone to diabetes mellitus than female. Methods: This cross-sectional, descriptive study was done in the Department of Anatomy, Dhaka Medical College, Dhaka, from August 2005 to December 2006, based on collection of 75 postmortem male human pancreas. The collected samples were divided into seven age groups: A (10-19 years), B (20-29 years), C (30-39 years), D (40-49years), E (50-59 years), F (60-69 years) and G (≥70 years). In histological slides, number of islets of Langerhans was measured by point counting technique per unit area of microscopic field and diameter by using ocular and stage micrometer. Results: The number of islets per unit area of the head of the pancreas were 1.40±0.55, 1.80±0.45, 1.40±0.55, 1.00±0.00, 1.80±0.45, 1.00±0.00and 1.20±0.45; in the body 1.20±0.45, 2.40±0.45, 2.00±0.00, 2.50±0.55,2.40±8.90, 2.20±0.45 and 2.00±0.00; in the tail region 2.40±0.55,3.00±1.22, 2.40±1.34, 2.80±0.84, 3.00±1.22, 2.80±0.84 and 3.20±0.45 in group A, B, C, D, E, F and G respectively. The diameter of pancreatic islets were found 82.64±0.73μm, 96.32±0.91μm, 108.52±8.76μm,135.20±8.38μm, 134.36±4.46μm, 102.40±0.89μm and 97.20±2.00μm in group A, B, C, D, E, F and G respectively. Conclusion: The number of the islets was much higher in tail than that of other regions. However, the diameter of the islets was found to increase up to 49 years and later decreased. Nepal Journal of Medical Sciences | Volume 03 | Number 01 | January-June 2014 | Page 63-37 DOI: http://dx.doi.org/10.3126/njms.v3i1.10361